Pengaruh Citra Lembaga dan Kepercayaan Donatur terhadap Keputusan Berdonasi pada Badan Amil Zakat Nasional Provinsi Kalimantan Selatan dengan Religiusitas sebagai Variabel Moderasi - Marhusin; Nur Hajijah; Kamila Windyani Putri (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: The aim of this study is to examine and analyze the impact of Institutional Image and Donor Trust on Donation Decisions at the National Amil Zakat Agency of South Kalimantan Province, with Religiosity as a Moderating Variable. The research is conducted at the National Amil Zakat Agency of South Kalimantan Province (Baznas Kal-Sel).The sample consists of 100 respondents, selected through random sampling, characterized as active Muzakki of Baznas Kal-Sel in 2024 who reside in South Kalimantan. Data collection was performed using questionnaires, and hypothesis testing was carried out using Smart-PLS analysis. The findings indicate that Institutional Image has a positive and significant effect on Donation Decisions, Donor Trust does not have a positive and significant effect on Donation Decisions, Religiosity has a positive and significant effect on Donation Decisions, Religiosity does not moderate the effect of Institutional Image on Donation Decisions, and Religiosity does not moderate the effect of Donor Trust on Donation Decisions at the National Amil Zakat Agency of South Kalimantan Province